Psychological Impacts of Natural Disaster - Malone, Judi L.; Linder, Jacqueline (Canadian Journal of Counselling and Psychotherapy, 2024)
The Canadian Red Cross approved funding for the Psychologists’ Association of Alberta through its Alberta Wildfires 2016 Community Organization Partnership Program. Funding was used to directly resource psychological trauma assessment and treatment until June 2020. Outcome-informed practices were employed to empirically validate treatment employing the Outcome Rating Scale (ORS). Sixteen approved psychologists provided trauma-informed services to 349 clients over 3 years, with the ORS being completed at five-session intervals. Results indicated very low levels of functioning and well-being at intake. For adults, overall average functioning and well-being increased over the treatment period. By the 5th, 10th, and 15th sessions, there was an average reported increase in perceived well-being of 65%, 57%, and 100%, respectively. Treatment made a significant difference for clients. The resulting five primary recommendations are 1) to provide timely access to qualified assessment and treatment, 2) to conduct trauma-informed screening of referrals, 3) to identify and provide additional resources for vulnerable populations, 4) to tailor services to gender considerations, and 5) to take steps to reduce barriers to accessing assessment and treatment.